Constructive Feminist Theology and Islamic Studies - Dhala, Mahjabeen (The Muslim world, 2025)
This essay examines the intersection of authenticity, autonomy, and diversity in Islamic feminist scholarship, challenging Western-centric paradigms in the study of Islam. It critiques secularist assumptions of critique and objectivity, revealing how they marginalize indigenous Muslim scholarly traditions and narratives, especially those of women. By integrating classical Islamic methodologies with critical feminist perspectives, the essay argues for the rich contributions of premodern Muslim women in theology and ethics. It emphasizes the need to center minoritized and indigenous voices and methodologies within Islamic studies, advocating for an inclusive approach that recognizes the vibrant diversity of Muslim traditions while addressing contemporary issues of gender, race, and justice.